Analysis of David Kolb's Learning Style According to Mathematical Representation Ability - Umi Hajaro; Akhmad Nayazik; Ratih Kusumawati (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The purpose of this study was to describe David Kolb's learning style according to the mathematical representation of students. This research is qualitative. The subjects of this study were students of class VIII SMP Agus Salim Semarang. The data were obtained by using the test method of the mathematical representation ability instrument, questionnaire of KLSI (Kolb Learning Style Inventory), interviews, and documentation. The results of this study are: (1). Students with High Mathematical Representation Ability tend to have an assimilator type of learning style, (2). Students with Medium Mathematical Representation Ability tend to have a converger learning style type, and (3). Students with Low Mathematical Representation Ability tend to have a divergent learning style. Teachers are suggested to identify students’ learning styles to be the best teachers for students. It is also recommended to collect mathematical representation-based problems to improve students' mathematical representation skills. Keywords: David Kolb, Mathematics Representation, Assimilator, Converger, Diverger